(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Willa Sibert Cather, Present study is an endeavour to explore Cather’s love for nature and her relation to it. Since nature as such is not the only focus of eco-critical studies of representation, other topics include frontiers, animals, cities, Indians and modernization, so this study would cover a wide range of issues, involving all that which comprises human interior and exterior contexts. Willa Sibert Cather deals with issues of identification human presence in the wilderness. She tries to achieve stability between nature and human beings by discussion of environmental communities. Cather’s writing presents nature and gentle as partners in green area. In her fiction, the natural and built environments are mixed up.